Product Innovation of Purple Sweet Potato Flour-Based Cookie Ingredients to Improve Product Quality - Kartika Dewi; Hanifah Salma, Farah; Abdul Ghani, Yosef (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2025)
Product innovation refers to the creation of products that have never existed before, with the aim of meeting customer needs and desires. The quality of a product is the level of compatibility between desires and needs and the specifications of the goods produced. Meanwhile, cookies are a type of food processed using flour as the main ingredient. To date, there have been many innovations in the addition of ingredients to cookies themselves. Alternative ingredients can be used as a substitute for wheat flour from local sources. The author chose purple sweet potatoes because they are known to have a short shelf life and spoil easily when left at room temperature. Therefore, the author decided to use purple sweet potatoes to make flour to extend their shelf life, given their high carbohydrate content and ease of processing. This study aims to explore and analyze innovations in the production process of purple sweet potato-based cookies to improve product quality. The object of this study is purple sweet potato flour as a substitute for wheat flour in cookie products. This study applies a descriptive method, with data collection techniques that include observation, interviews, and literature review. The research sample consisted of 20 respondents selected through sampling, which included a consumer panel and a children's panel to evaluate purple sweet potato-based cakes through sensory testing. Consumer responses were evaluated based on the taste, texture, and aroma of purple sweet potato-based cakes. The results of this study indicate that product innovation has an impact on product quality.